Tinjauan Maslahah Terhadap Praktik Pembatalan Sepihak Dalam Sistem Jual Beli Pre-Order - Dessy Asnita; Syarifah Mudrika; Agustinar; Ryzka Dwi Kurnia; Asih Pertiwi (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2025)
The Pre-Order (PO) system in e-commerce offers convenience for manufacturers and consumers by allowing the ordering of goods before they are produced. From the perspective of maslahah, this system can provide benefits such as production efficiency, reduction of the risk of excess stock, and certainty of demand for producers. However, in practice, PO systems also face serious challenges, especially in terms of unilateral cancellations by consumers, late payments, and failure of manufacturers to fulfill orders. This disorder can cause financial losses and lower trust in business transactions, so it needs to be studied through the perspective of maslahah to assess the extent of the benefits and harms. This study uses a phenomenological qualitative method, by examining the experience of producers in dealing with irresponsible practices in the PO system. Data was obtained through in-depth interviews and literature studies related to Islamic law in business transactions. The analysis is carried out based on three levels of maslahah: dharuriyyah, hajiyyah, and tahsiniyyah. The results of the study show that the PO system has great benefits for the digital economy, but it also risks causing harm if it is not properly regulated. Therefore, solutions such as strengthening digital contracts, transparency in agreements, and implementing a stricter payment system are needed to protect the rights of producers and consumers. With this approach, the PO system can continue to run fairly and sustainably in accordance with the principles of justice, trust, and benefit in Islamic muamalah.